The Translanguaging Pedagogy 4.0, An Innovative Pedagogical Model for Multilingual and Multicultural Classrooms in the Philippines: The Case of Sulu State University - Tulawie, Alnadzma (International Journal of Arts, Sciences and Education, 2026)
In the context of the Philippines as an inherently multilingual and multicultural nation, the education system continues to face the challenge of developing pedagogical approaches that meaningfully address learners’ linguistic and cultural diversity. This paper aims to develop and articulate Translanguaging Pedagogy 4.0, an innovative pedagogical model grounded in translanguaging theory, digital pedagogy, culturally responsive teaching, and Education 4.0 frameworks. Using a qualitative integrative research design, the study systematically examined selected empirical and theoretical literature to identify the core principles, dimensions, and pedagogical implications of the model for teaching in multilingual multicultural classrooms in the Philippine context. Findings reveal four key dimensions of Translanguaging Pedagogy 4.0: (1) the dynamic use of language as a learning resource, (2) the integration of digital and hybrid learning environments, (3) the cultural anchoring of knowledge and curriculum content, and (4) the promotion of critical and inclusive learner participation. The study demonstrates that Translanguaging Pedagogy 4.0 holds strong potential as a contextualized and innovative framework for advancing decolonized, inclusive, and meaningful education in the Philippines.